Decision Support System in the Best Selection Coffee Shop with TOPSIS Method - Reflan Revife Purba; Mesran Mesran; Mohammad Taufan Asri Zaen; Setiawansyah Setiawansyah; Dodi Siregar; Erlin Windia Ambarsari (The IJICS (International Journal of Informatics and Computer Science), 2023)
The development of business opportunities in today's era brings many benefits as well as in coffee shops. Coffee Shop is a place to relax or gather with friends, family to release boredom, after daily activities, and Coffee shop enthusiasts are quite well known both from teenagers to parents, where coffee shop fans must have an ability to visit the coffee shop. This research has a goal to generate a decision support system (DSS). Which is where the decision support system (DSS) has utility as a tool to make the best coffee shop decisions overall. By setting the TOPSIS (Technique For Order Preference By Similarity To Ideal Solution) method by getting the preference value as the first rank. So with this, the best coffee shop is found in alternative A04 with the highest score of 0.9911 on behalf of Arata Coffee